The impact of independent auditors’ tax consulting services on tax litigation - Martinez, Antonio Lopo; Nascimento, Marielza Santos do; Santos, Luis Paulo Guimarães dos; Nakao, Silvio Hiroshi; Andrade, Aline Mendonça de (REVISTA AMBIENTE CONTÁBIL - Universidade Federal do Rio Grande do Norte - ISSN 2176-9036, 2026)
Purpose: This study aims to determine the impact of tax consulting services provided by independent auditors on the incidence of tax litigation among Brazilian companies listed on B3. The research investigates whether increased investment in auditing and tax consulting services is associated with a higher likelihood of legal disputes. Methodology: An empirical analysis was conducted using a balanced panel dataset comprising 416 observations from 2017 to 2020. We used multiple linear regression models, as well as descriptive statistics and Pearson correlation analysis. In addition, the study held constant several important variables, including the return on equity (ROE), indebtedness, and firm size, to isolate the impact of tax consulting expenditures on tax litigation outcomes. Results: It shows a highly positive relationship between higher spending on auditing and on tax consulting services and the incidence of tax litigation. More specifically, firms that invest more in these services face more tax-related legal disputes. These findings suggest that, while tax consulting may provide strategic and compliance-related benefits, it also increases exposure to litigation risks. Contributions of the Study: This article addresses an important theoretical gap in the literature by establishing a direct connection between the provision of tax consulting services by independent auditors’ and enhanced legal exposure. At a methodological level, the use of panel data econometric models increases both the precision and robusteness of the analysis, offering deeper insights into the driversof tax litigation. The research contributes to academic literature in accounting, auditing, and corporate governance, while providing practical implications for regulators and corporate managers aiming to balance the strategic benefits related to tax consulting with effective risk mitigation.